Factors related to 6-month mortality after the first-ever stroke - Ehsan Sarbazi; Parvin Sarbakhsh; Daryoush Savadi Oskooei; Mohammad Yazdchi; Saber Ghaffari-Fam; Seyed Morteza Shamshirgaran (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND AND OBJECTIVE: Stroke is the second leading cause of death worldwide and the number of stroke cases has increased remarkably over the last 20 years. This study aimed at identifying predictors of with 6-month mortality of first-ever stroke patients and the factors contributing to it in East Azerbaijan province. MATERIALS AND METHODS: A closed cohort study was carried out from April 2014 to December 2014. All cases of first-ever diagnosed stroke were included in the study. Any transient ischemic attack, silent brain infarctions, and the stroke cases which were neither associated with trauma, blood disease nor with malignancy were excluded from the study. The variables of this study include participants' demographic characteristics, stroke severity National Institutes of Health Stroke Scale (NIHSS), and stroke risk factors. Patients were followed up within 6 months. To determine the survival time, the log-rank method was applied to compare intergroup differences. The tests include the univariate and multivariate analysis Cox regression. P < 0.05 were considered as statistically significant. RESULTS: A total of 576 cases of stroke were included in this study. Average age of ischemic and hemorrhagic stroke was 70.15 ± 13.0 and 67.79 ± 12.69, respectively. Case-fatality rate (CFR) of stroke patients was 49.2 and 21.7% in hemorrhagic and ischemic stroke types, respectively. Factors contributing to stroke mortality events include the severity of stroke (NIHSS categories 15-19 and ≥20), age over 65, being female, high body mass index and hyperlipidemia. In the final model, the severity of stroke (with NIHSS 15-19 with hazard ratio (HR) 4.22 (95% confidence interval [CI] 2.36-7.56) and NIHSS ≥20 with HR 5.34 (95% CI: 2.81-10.12) and age above 65 with HR 1.61 (95% CI: 1.02-2.51) were the most important predictors of 6-month mortality. CONCLUSION: Severity of stroke by NIHSS was the most prominent factor in stroke patients' mortality. By increasing the follow-up time, a better evaluation of the predictors of mortality after stroke can be achieved.